การเพิ่มคุณภาพและความปลอดภัยอาหารทะเลและผลิตภัณฑ์ - สุทธวัฒน์ เบญจกุล (มหาวิทยาลัยสงขลานครินทร์, 2022)
Quality and safety of seafoods are the prime factors affecting consumers and economy. Improvement or development of potential technologies or utilization of seafood processing byproducts is of profound benefit for seafood industry of Thailand. Collagen could be extracted from fish scale, or skin of fish or squid using acid or acid in combination of pepsin, especially with the aid of ultrasound. Facing with fishy odor, which is the drawback of fish gelatin, it must be produced from fresh raw materials. Defatting along with the use of antioxidant during the extraction could lower the development of fish odor in gelatin. Additionally, some hydrocolloids or phenolic extracts were incorporated to strengthen the gelatin gel. Apart from serving as gelling agent, gelatin could be used for film making. With poor water vapor barrier property, the improvement of gelatin film was carried out by addition of oil, development of gelatin/polylactic acid (PLA) bilayer films or nanoclay composite film, etc. Protein hydrolysates possessing bioactivities were successfully produced from fish processing leftover via the optimization of process, degree of hydrolysis and type of proteases. Hydrolysate subjected to Maillard reaction exhibited the increased bioactivity. Hydrolysates could be applied or fortified in drink and surimi product, etc. Marine oils rich in W-3 fatty acids were extracted from hepatopancreas of Pacific white shrimp or defat fat of seabass. Microencapsulation was a powerful tool in enhancement of stability and microcapsule could be applied with ease. Addition of phenolic extract effectively increased oxidative stability of marine oil emulsion. Gel strength of surimi was increased via the addition of protease inhibitors from various sources such as duck egg albumen, squid ovary, tuna roe and legume seeds. Furthermore, protein cross-linkers such as ethanolic coconut husk extract could increase gel strength. Squid melanin free ink containing tyrosinase was able to increase gel strength of surimi. Additionally, it could prevent lipid oxidation and improve the property of fish muscle protein based films. Phosphate and bicarbonate replacer was developed and was able to increase water holding capacity and lower the cooking loss of treated shrimp. Nevertheless, it induced the formation of fishy odor. It had no effect in color of pre-cooked shrimp and increased freeze-thaw stability. For melanosis in precooked shrimp, it was retarded by treatment with phenolic compounds with the aid of ultrasound, in which the active compounds could be penetrated into the shrimp more effectively. Under-utilized species such as small shrimp, Acetes vulgaris, could be used as an alternative raw material for kapi production. The kapi obtained had the quality equivalent to the commercially available counterpart. Trypsin from fish viscera could be recovered and applied for several purposes, e.g. processing aid for virgin coconut oil production, etc.